2011
DOI: 10.1007/s00338-011-0864-x
|View full text |Cite
|
Sign up to set email alerts
|

Description of viral assemblages associated with the Gorgonia ventalina holobiont

Abstract: The diversity and function of viruses in coral holobionts has only recently received attention. The nonreef building gorgonian octocoral, Gorgonia ventalina, is a major constituent of Caribbean reefs. We investigated viral communities associated with G. ventalina tissues to understand their role in gorgonian ecology. Pyrosequencing was used to prepare a total of 514,632 sequence reads of DNA-and RNA-based mixed-community viral genomes (metaviromes). RNA viral assemblages were comprised of primarily unidentifia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Of these, between 0.06 and 88.03% matched viral genomes, with the remaining sequences corresponding to bacterial, archaeal, or eukaryotic genome fragments. This is similar to the results of previous studies that utilized similar viral genome isolation protocols, and likely results from DNA released from host, bacterial, and/or archaeal cells during the tissue homogenization process (Hewson et al, 2011a(Hewson et al, , 2013Gudenkauf et al, 2014). The low number of viral annotations may be a result of lack of representative viral genomes in public databases (Weynberg et al, 2014).…”
Section: Metagenomic Annotationsupporting
confidence: 78%
See 1 more Smart Citation
“…Of these, between 0.06 and 88.03% matched viral genomes, with the remaining sequences corresponding to bacterial, archaeal, or eukaryotic genome fragments. This is similar to the results of previous studies that utilized similar viral genome isolation protocols, and likely results from DNA released from host, bacterial, and/or archaeal cells during the tissue homogenization process (Hewson et al, 2011a(Hewson et al, , 2013Gudenkauf et al, 2014). The low number of viral annotations may be a result of lack of representative viral genomes in public databases (Weynberg et al, 2014).…”
Section: Metagenomic Annotationsupporting
confidence: 78%
“…Because benthic invertebrates play important roles in marine habitat ecology and biogeochemistry, investigation into the viral diversity of their microbiomes is relevant to understanding how viruses influence marine ecosystems. There have been few reports of viruses of echinoderms Hewson et al, 2014), very few of non-commercially important (but ecologically important) marine arthropods (e.g., Dunlap et al, 2013), only one of viruses infecting non-scleractinian corals (Hewson et al, 2011a), and no previous reports of viruses inhabiting urochordates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, local anthropogenic impacts do not seem to be the cause for the bacterial shifts simultaneously observed in the 3 sites in summer 2007, although a monitoring of environmental parameters and microbial community structure in the water column would be required to better evaluate differences between the sites. Finally, the factors that could have directly or indirectly caused a transient change in the natural bacterial community remain unclear and several other hypotheses cannot be ruled out, such as a bacteriophage infection targeting Hahellaceae and causing microbial mortality [66], or the occurrence of subtle alterations in gorgonian physiology in summer [67] that would disrupt the host-bacteria relationship without macroscopic disease signs.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have reported the metagenomic identification of novel viruses in P. monodon, in Farfantepenaeus duorarum, in copepods and in bivalves [7,[14][15][16][17]. Apart from these economically important species, few studies were published concerning the viromes of ecological important marine invertebrates, such as ghost and volcano shrimps, tunicates, non-scleractinian corals, amphipods and echinoderms [18][19][20][21][22]. However, recent comprehensive surveys have been conducted to discover the genomic diversity of multiple DNA and RNA viruses in arthropods, including marine species [23][24][25].…”
Section: Introductionmentioning
confidence: 99%